Efektivitas Psikoedukasi dan Token Ekonomi terhadap Pengurangan Konsumsi Gula Secara Berlebihan - Salma Syakira; Rida Yanna Primanita (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study was conducted to evaluate the effectiveness of psychoeducation and token economy methods to reduce excess sugar consumption in individuals. This research method uses a one group pretest-posttest experimental design. The intervention included psychoeducation to increase understanding of the dangers of excessive sugar consumption and token economy to modify the subject’s behavior. Based on the experiment, result showed that psychoeducation significantly improved subjects’ understanding of the dangers of excessive sugar consumption (p=0.011). However, the token economy did not show significant changes in sugar consumption (p=0.655). These findings suggest the need for a longer and more sustained intervention approach. This study provides guidance on the development of psychology based health strategies to support long-term behavior change.